Strategies For Organization In Educational Resource Management - Novianti; Sophia Tri Satyawati; Yari Dwikurnaningsih (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2024)
This study aims to analyze organizational strategies in managing educational resources at SMK Karmel Tangerang, Banten. The primary focus of this research is on the organization of educators, facilities and infrastructure, as well as educational financing. The method used is descriptive qualitative, with data collection techniques including interviews, observations, and documentation. The findings indicate that SMK Karmel Tangerang has implemented effective organizational strategies in managing human resources, facilities, and budgets. Mapping educators based on their competencies, regular maintenance of educational facilities, and transparent budget management are strengths in the school’s management. However, this study also identified several challenges in inter-departmental coordination, which can affect the operational effectiveness of the school. Therefore, it is recommended to improve communication and coordination among school components to enhance the effectiveness of organization in supporting the achievement of optimal educational goals.